EVALUASI BELAJAR PENDIDIKAN DASAR 9 TAHUN MELALUI MADRASAH DI KABUPATEN PANDEGLANG - K. SUKARDJI (Al Qalam, 2001)
In the Framework to raise the progress of the nation life entirely, the goverment has carried out the nine years - Basic Education Compulsory Programme (Wajar Dikdas) through general school and Islamic school In this programme through the Islamic school among others have been done in model school of Islamic elementery school (MIN) in village of part, Mandalawangi, Pandeglang and the Islamic secondary private scool "Cidangiang" Kota Pandeglang., Pandeglang.The Nine Years - Basic Education Compulsory Programme through Islamic School has been applied on the Islamic School (MI and MTs) by providing service of education to all basic education school age from any economic sosial backgrounds, both living in the countryside and the town around the two schools evironments. Both children coming from the poor and the rich family Have equal chance to obtain service of education from two schools.To support the operational of programme among parents, school and group of society/foster parents (GNOTA) and government have colleted fund to run the education at the school, including the school payment for students by the cooperation in colleting the fund wich have been done by many parts for costing the programme so that in can run smoothly and succesfully.Key words: Evaluation, Compulsory Education, Madrasah, Pandeglang.